Ultraviolet Radiation and Basal Cell Carcinoma: An Environmental Perspective - Teng, Yan; Yu, Yong; Li, Sujing; Huang, Youming; Xu, Danfeng; Tao, Xiaohua; Fan, Yibin (Frontiers in Public Health, 2021)
Ultraviolet radiation (UVR) is a known carcinogen participated for the development of skin cancers. Solar UVR exposure, particularly ultraviolet B (UVB), is the mostly significant environmental risk factor for the occurrence and progress of basal cell carcinoma(BCC). Both cumulative and intermittent high-grade UVR exposure could promote the uncontrolled replication of skin cells. There are also exsiting other contributing environmental factors that combine with the UVR exposure to promote the development of BCC. DNA damage in formation of skin cancers is considered to be a result of UVR toxicity. It is UVR that could activate a series of oncogenes simultaneously inactivating tumor suppressor genes and aberrant proliferation and survival of keratinocytes that repair these damages. Furthermore, mounting evidence demonstrates that inflammatory responses of immune cells in the tumor microenvironment plays crucial role in the skin tumorigenesis as well. In this chapter, we will follow the function of UVR in the onset and development of BCC. We describe the factors that influence BCC induced by UVR, and also review the recent advances of pathogenesis of BCC induced by UVR from the genetic and inflammatory aspects.